2009
DOI: 10.1111/j.1365-2923.2009.03496.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence in medical students: does it correlate with selection measures?

Abstract: This study offers information that can be used to compare the EI scores of medical students with those of other health professionals. No relationship was identified between cognition (measured by the UMAT) and skill (measured by the MSCEIT) in the interpersonal domain and EI. Further studies are required to explore whether UMAT Section 2 is measuring EI, if there are associations between EI and academic performance and if EI can be used to predict the performance of junior doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
1
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 28 publications
(47 reference statements)
6
57
1
5
Order By: Relevance
“…Based on the lack of current understanding around what is assessed through various EI measures, and which would be most appropriate for educational institutions, it would appear that such tools are risky instruments to use for admissions purposes at this point in time. In addition to the findings of the current study, this assertion is further supported by recent studies which also failed to find a relationship between EI measures and admissions tests (Carr 2009;Kulasegaram et al 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Based on the lack of current understanding around what is assessed through various EI measures, and which would be most appropriate for educational institutions, it would appear that such tools are risky instruments to use for admissions purposes at this point in time. In addition to the findings of the current study, this assertion is further supported by recent studies which also failed to find a relationship between EI measures and admissions tests (Carr 2009;Kulasegaram et al 2009).…”
Section: Discussionsupporting
confidence: 89%
“…This is comparable to a survey 13 demonstrating that Asian medical students were less assertive and more reticent than other racial/ethnic cohorts. A recent study 14 on emotional intelligence using the Mayer-Salovey-Caruso Emotional Intelligence test also suggested that Asian medical students had higher emotional intelligence scores. These demographic findings may emphasize the importance of local customs, traditions and cultural preferences, or communication influences on behavior.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were reported by Bastian et al (2005) and Tyagi (2004), who found no gender difference in EI. However, several studies have reported that women are emotionally more intelligent than their male counterparts (Ciarrochi 2001;Palmer et al 2003;Day & Carroll 2004;Carr 2009). Caution should be exercised when comparing the findings of the current study with those of previous ones, as the present study used subscale scores rather than overall EI scores.…”
Section: Discussionmentioning
confidence: 99%